Penentuan Strategi Pemasaran Produk Griya Hasanah BSI KCP Tangerang Villa Melati Mas: Pendekatan Analisis SWOT - Jamaludin, Nur; Tidjani, Shofiah; Permatasari, Yovika; Simatupang, Aisyah Defy R. (Jurnal Ekonomi Syariah Pelita Bangsa, 2024)
A strong marketing strategy is crucial for firms since it immediately affects sales growth, brand promotion, and the identification of new market opportunities, leading to a sustained competitive advantage. Using SWOT analysis, which includes assessing strengths, weaknesses, opportunities, and threats, is a crucial tool for developing a focused marketing strategy for items. This study seeks to explore the utilization of SWOT analysis in formulating the marketing strategy for the Griya Hasanah Home Financing Product (PPR) at BSI KCP Tangerang Villa Melati Mas. It involves a thorough analysis of both internal (strengths and weaknesses) and external (opportunities and threats) variables. This research aims to use a descriptive qualitative technique to thoroughly examine and analyse the strengths, flaws, opportunities, and dangers associated with the Griya Hasanah PPR product at Bank Syariah Indonesia KCP Tangerang Villa Melati Mas. Data collecting involves gathering primary sources, such as interviews, as well as secondary data obtained from other sources such websites, journals, books, and pertinent literature. The study's findings indicate that when using the SWOT analysis framework, internal factors (strengths and weaknesses), referred to as S - W, have a favourable value of 1.08 on the X-axis. On the other hand, external factors (opportunities and threats), represented as O - T, have a positive value of 1 on the Y-axis. Therefore, placing the Griya Hasanah PPR product at BSI KCP Tangerang Villa Melati Mas in quadrant 1 indicates the necessity for the company to implement a proactive marketing plan. By utilizing the company's strengths and capitalising on opportunities, this strategy is positioned to strengthen its competitive position and continuously extend its market presence.